Pengaruh Keberadaan Perkebunan Kelapa Sawit (PT.Tani Prima Makmur) terhadap Kondisi Sosial Ekonomi Karyawan di Desa Mendikon Kecamatan Amonggedo Kabupaten Konawe - Said, Hikmal; Yunus, Lukman; Yusria, Wa Ode (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to determine the socio-economic conditions of employees after the establishment of oil palm plantation company (PT Tani Prima Makmur) in Mendikonu Village Amonggedo District Konawe District. This research was conducted in Mendikonu Village, Amonggedo Sub-District, Konawe District. The population in this research is the people who work as employees in oil palm plantation companies. Determination of the sample in this study was conducted by using the census method, which took as many as 43 families, who entered work as employees in oil palm plantation companies. The census method is characterized by the consideration that the entire population is taken as a sample of the study if the total population is less than 50 persons. The results of this study show that: the influence of oil palm plantation companies on the socio-economic life of employees is a very positive effect. It is said to have a positive effect because in view of the existence of oil palm plantations can improve good social relations in the midst of community life. In addition to social influences also affect the economic life where the income of the people who work as local employees, especially those who work as oil palm fruit harvesters on average increased to, Rp.1.981.370 per month, while the employees working as the average foreman increased to become Rp.2.340.000 per month.